Client and Therapist Interpersonal Behaviour in Cognitive Therapy for Depression - Thompson, Katherine; Schwartzman, Deborah; D’Iuso, Debora; Dobson, Keith; Drapeau, Martin (Canadian Journal of Counselling and Psychotherapy, 2018)
Individuals with depression can be interpersonally submissive, avoidant, unassertive, and aggressively hostile, characteristics that contribute to strained relationships with significant others. Although therapists’ ability to implement effective interventions while maintaining dyadic cohesion is integral to treatment outcome, those working with depressed clients may face particular challenges related to the interpersonal style prevalent in this clinical population. This study examined the interpersonal behaviour of clients and therapists in cognitive therapy for depression using Structural Analysis of Social Behavior (SASB; Benjamin, 1974). Therapist interpersonal behaviour differed significantly across time and clinicians. As well, client hostility in early sessions was associated with treatment outcome. Post-hoc analyses suggest that client hostility was correlated with both compliance and assertion.